Hypoxia-Inducible Factor 2-Dependent Pathways Driving Von Hippel–Lindau-Deficient Renal Cancer - Meléndez-Rodríguez, Florinda; Roche, Olga; Sanchez-Prieto, Ricardo; Aragones, Julian (Frontiers in Oncology, 2018)
The most common type of the renal cancers detected in humans is clear cell Renal Cell Carcinomas (ccRCCs). These tumors are usually initiated by biallelic gene inactivation of the Von Hippel Lindau (VHL) factor in the renal epithelium, which deregulates the hypoxia inducible factors (HIFs) HIF1α and HIF2α, and provokes their constitutive activation irrespective of the cellular oxygen availability. While HIF1α can act as a ccRCC tumor suppressor, HIF2α has emerged as the key HIF isoform that is essential for ccRCC tumor progression. Indeed, preclinical and clinical data have shown that pharmacological inhibitors of HIF2α can efficiently combat ccRCC growth. In this review, we discuss the molecular basis underlying the oncogenic potential of HIF2α in ccRCC by focusing on those pathways primarily controlled by HIF2α that are thought to influence the progression of these tumors.